Money Targeting in a Modern Forecasting and Policy Analysis System : an Application to Kenya - Andrle, Michal; Berg, Andrew; Berkes, Enrico; Portillo, Rafael (Washington, D.C. : International Monetary Fund, 2013)
We extend the framework in Andrle and others (2013) to incorporate an explicit role for money targets and target misses in the analysis of monetary policy in low-income countries (LICs), with an application to Kenya. We provide a general specification that can nest various types of money targeting (ranging from targets based on optimal money demand forecasts to those derived from simple money growth rules), interest-rate based frameworks, and intermediate cases. Our framework acknowledges that ex-post adherence to targets is in itself an objective of policy in LICs; here we provide a novel interpretation of target misses in terms of structural shocks (aggregate demand, policy, shocks to money demand, etc). In the case of Kenya, we find that: (i) the setting of money targets is consistent with money demand forecasting, (ii) targets have not played a systematic role in monetary policy, and (iii) target misses mainly reflect shocks to money demand. Simulations of the model under alternative policy specifications show that the stronger the ex-post target adherence, the greater the macroeconomic volatility. Our findings highlight the benefits of a model-based approach to monetary policy analysis in LICs, including in countries with money-targeting frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet